2019
DOI: 10.1016/j.radcr.2019.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Ducts of Luschka as a rare cause of postoperative biloma. MRCP findings

Abstract: Laparoscopic cholecystectomy can be complicated by a post- operative biloma. Bile leak from the duct of Luschka is reported to be the second most frequent cause, reported in 0.15%-2% of the patients. This case report aims to underline the significance of this anatomic variation and how the management of the aforementioned complication can be facilitated by MRI- MRCP. A 78 year old male patient underwent an elective laparoscopic cholecystectomy and was found to have a post-operative biloma. An MRCP was carried … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…1,2 Studies have suggested that subvesicular duct injury may occur in only 0.15% to 2% of patients undergoing laparoscopic cholecystectomy; however, it is one of the most common causes of a postcholecystectomy bile leak. [1][2][3][4] As such, it is important to recognize the imaging manifestations of accessory duct injury to appropriately guide patient management. While ERCP and MRCP are both sensitive and specific at identifying an accessory duct in the setting of suspected injury, 5,6 hepatobiliary scintigraphy has traditionally been used only as a binary test to detect whether a leak is present or not.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 Studies have suggested that subvesicular duct injury may occur in only 0.15% to 2% of patients undergoing laparoscopic cholecystectomy; however, it is one of the most common causes of a postcholecystectomy bile leak. [1][2][3][4] As such, it is important to recognize the imaging manifestations of accessory duct injury to appropriately guide patient management. While ERCP and MRCP are both sensitive and specific at identifying an accessory duct in the setting of suspected injury, 5,6 hepatobiliary scintigraphy has traditionally been used only as a binary test to detect whether a leak is present or not.…”
mentioning
confidence: 99%
“…A subvesical bile duct, often referred to as a duct of Luschka, is a small accessory duct that courses along the gallbladder fossa and drains into the right hepatic or common hepatic duct 1,2 . Studies have suggested that subvesicular duct injury may occur in only 0.15% to 2% of patients undergoing laparoscopic cholecystectomy; however, it is one of the most common causes of a postcholecystectomy bile leak 1–4 . As such, it is important to recognize the imaging manifestations of accessory duct injury to appropriately guide patient management.…”
mentioning
confidence: 99%